The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.inorgchem.0c01150
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of 12-Tungstovanadate-Templated Nanocage and Nanocomposites with Single-Walled Carbon Nanotubes as Anodes in Lithium-Ion Batteries

Abstract: A new 12-tungstovanadate-templated 3D nanocage framework, Ag 10 (μ 4 -ttz) 4 (H 2 O) 4 (VW 12 O 40 ) (VW 12 @MOCF), was designed based on a "molecular library", hydrothermally synthesized, structurally characterized, and explored as anode material for lithium-ion batteries (LIBs). Combination of the structural superiority of VW 12 @MOCF with the good electrical conductivity of the single-walled carbon nanotubes (SWNTs) renders the VW 12 @MOCF/SWNT-2 nanocomposite reasonable electrochemical performance and stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Recent reports indicate that tungstovanadates can exhibit special structural features and properties. Herein, we provide a new method for the preparation of a novel TRIS-substituted Lindqvist-type hexatungstovanadates [V x W 6– x O 16 (CH 2 O) 3 CR] ( x −1)– [ x = 3 or 4; R = CH 3 ( 1 ; CCDC 2027592) or CH 2 OH ( 2 ; CCDC 2027593)]. These compounds were synthesized by a simple one-pot reaction in an aqueous solution with simple vanadate, tungstate salts, and TRIS ligands under mild conditions.…”
mentioning
confidence: 99%
“…Recent reports indicate that tungstovanadates can exhibit special structural features and properties. Herein, we provide a new method for the preparation of a novel TRIS-substituted Lindqvist-type hexatungstovanadates [V x W 6– x O 16 (CH 2 O) 3 CR] ( x −1)– [ x = 3 or 4; R = CH 3 ( 1 ; CCDC 2027592) or CH 2 OH ( 2 ; CCDC 2027593)]. These compounds were synthesized by a simple one-pot reaction in an aqueous solution with simple vanadate, tungstate salts, and TRIS ligands under mild conditions.…”
mentioning
confidence: 99%
“…As we know, POM‐based materials show extraordinary advantages for LIBs [65–67] . However, many factors (such as different chemical components) that might influence electrochemical performance still need to be verified [68] .…”
Section: Resultsmentioning
confidence: 99%
“…As we know, POM-based materials show extraordinary advantages for LIBs. [65][66][67] However, many factors (such as different chemical components) that might influence electrochemical performance still need to be verified. [68] In this respect, the design of specifically targeted compounds often plays an important role in the in-depth study of this issue.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…38−42 For example, Sha et al reported a 12-tungstovanadate framework combined singlewalled carbon nanotube (SWNT) composite (VW12@MOCF/ SWNT-2), which featured the outstanding electrochemical performance. 43 The reduced graphene oxide (RGO)/conducting polymers could interact with POMOFs via hydrogen bonds and π−π interactions to effectively enhance the POMOF conductivity. 44,45 On the other hand, the sizes of the resulting composites could affect the rate performance of LIBs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this facet, the most popular method is to combine POMOFs with a conducting substrate. For example, Sha et al reported a 12-tungstovanadate framework combined single-walled carbon nanotube (SWNT) composite (VW12@­MOCF/​SWNT-2), which featured the outstanding electrochemical performance . The reduced graphene oxide (RGO)/​conducting polymers could interact with POMOFs via hydrogen bonds and π–π interactions to effectively enhance the POMOF conductivity. , On the other hand, the sizes of the resulting composites could affect the rate performance of LIBs. The nanoscale samples provided a large amount of specific surfaces for the interactions with active sites of Li + , which thus improved their electrochemical behaviors for LIBs. , However, the size-controlled syntheses for the POMOFs are difficult and essential for anode materials. , …”
Section: Introductionmentioning
confidence: 99%